Generating Mouse Models Using CRISPR‐Cas9‐Mediated Genome Editing. Issue 1 (1st March 2016) - Qin, Wenning; Kutny, Peter M.; Maser, Richard S.; Dion, Stephanie L.; Lamont, Jeffrey D.; Zhang, Yingfan; Perry, Greggory A.; Wang, Haoyi
Abstract: The CRISPR‐Cas9 system in bacteria and archaea has recently been exploited for genome editing in various model organisms, including mice. The CRISPR‐Cas9 reagents can be delivered directly into the mouse zygote to derive a mutant animal carrying targeted genetic modifications. The major components of the system include the guide RNA, which provides target specificity, the Cas9 nuclease that creates the DNA double‐strand break, and the donor oligonucleotide or plasmid carrying the intended mutation flanked by sequences homologous to the target site. Here we describe the general considerations and experimental protocols for creating genetically modified mice using the CRISPR‐Cas9 system. © 2016 by John Wiley & Sons, Inc.